2018
DOI: 10.3390/met8050369
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Induced Plasticity Effects of a Non-Equal Molar Co-Cr-Fe-Ni High Entropy Alloy System

Abstract: Metastability-engineering strategy is an important topic for high entropy alloys (HEAs), owing to the transformation-induced plasticity effect (TRIP). In this work, TRIP effects of Co-Cr-Fe-Ni HEAs are investigated. Results indicate the tensile deformation-induced martensitic transformation occurs in Co 35 Cr 25 Fe 40−x Ni x (x = 0-15 at %) HEAs. The excellent combination of tensile strength (760 MPa-1000 MPa) and elongation (65-35%) owe to solid solution strengthening of Co and Cr, and the TRIP effect. In non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
(56 reference statements)
2
17
0
Order By: Relevance
“…These trends are, however, not observed for Mn-containing HEAs, as pointed out in Refs. [31,33] and also in the present work. The present three Mn-containing HEAs confirm that the correlation between VEC and TRIP probability is weak.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These trends are, however, not observed for Mn-containing HEAs, as pointed out in Refs. [31,33] and also in the present work. The present three Mn-containing HEAs confirm that the correlation between VEC and TRIP probability is weak.…”
Section: Discussionsupporting
confidence: 82%
“…Chen et al [32] confirmed similar trends for CrFeCoNi-based HEAs with Al, Cu, and Mo but again without Mn. Fang et al [33] have found that CrFeCoNi-based HEAs without Mn are prone to show TRIP when VEC≈8 due to the metastability of the fcc phase. These trends are, however, not observed for Mn-containing HEAs, as pointed out in Refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valence-electron concentrations (VECs) of HEAs have been previously discussed in relation to phase stabilities [56][57][58][59]. In the present study, the VEC of each alloy was computed as the average of the VECs of the constituent elements weighted by their concentrations in atomic percent, where the VECs of the elements in groups 4, 5, and 6 were taken as 4, 5, and 6, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It should be noted that the hardening rates of carbon-free (NiCo) 75 Cr 17 Fe 8 and low carbon (NiCo) 75 Cr 17 Fe 8 C 0.34 alloy even increased with strain in the strain range of 0.1-0.6 at 77 K. The plateau or hump of strain hardening rate in Figure 6 suggests the activation of a new deformation defect which can act as both deformation obstacles and deformation carriers. The increase of strain hardening rate with strain has been observed in various twin-induced plasticity (TWIP) [32][33][34][35] and transformation-induced plasticity (TRIP) alloys [34]. The excellent strength and ductility of (NiCo) 75 Cr 17 Fe 8 and low carbon (NiCo) 75 Cr 17 Fe 8 C 0.34 alloy in Figure 5 is attributed to the increase of strain hardening rate with strain in the strain range of 0.1-0.6 at 77 K. The tensile strength increased significantly up to~1400 MPa in carbon-containing (NiCo) 75 Cr 17 Fe 8 C 0.83 with a decent ductility of 106.…”
Section: Effect Of Carbon Addition On the Mechanical Propertiesmentioning
confidence: 99%